The Building of Main Character's Self-Actualization through Religion in Hermann Hesse's Siddharta (Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
The purpose of this study is to find out the role of religion in Siddhartha's self-actualization process in Hesse` Siddhartha. The analysis applies Rogers' humanistic psychology focusing on self-actualization. The method used was qualitative with content analysis. The data were taken from the texts contained in the novel. Data analysis used triangulation techniques. The results showed that Buddhism and Hinduism had taught various things through religious activities conducted by Siddhartha to find out his actualization.